An Analysis of Financial Statements Assets Financial Perfomance at Pt. Elap In Pendopo Sub-District, Empat Lawang Regency - Yulita Sari; Yun Fitriano; Yudi Irawan Abi (Penerbit Jurnal Indonesia, 2024)
The purpose of this study is to provide an assessment of financial performance, seen from the analysis of financial ratios consisting of liquidity ratios, solvency ratios and profitability ratios. The research method used is descriptive quantitative, namely data obtained and analyzed on the basis of existing theories so as to provide a fairly clear description and calculation. This research was conducted using documentation and in-depth interviews. The assessment of financial performance in this study uses liquidity ratio analysis consisting of current ratio and quick ratio, solvency ratio consisting of debt to asset ratio and debt to equity ratio and profitability ratio consisting of return on assets and return on equity. Based on the results of the analysis carried out, it shows that the performance and financial position can be said to be less good in liquidity ratios, still not good enough in solvency ratios and still not good enough in profitability ratios. While the profitability ratio level is still below the industry average, so it can be said that the company is still not optimal in generating profits.